Pengaruh Organisasi Masyarakat Terhadap Pemerintahan Desa - Ahmad Rizki; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to analyze the influence of community organizations on the performance and governance of village administration. Community organizations, as part of the active social elements in village life, play an important role in supporting, supervising, and providing input on the governance of the village. This research uses a qualitative approach with a case study method in several villages in the region of Karawang Regency, and is supported by secondary data from journals and previous research reports. Research results show that active involvement of community organizations can enhance transparency, accountability, and public participation in decision-making at the village level. However, this influence heavily depends on the extent to which community organizations have institutional capacity and constructive relationships with village authorities. The conclusion of this study emphasizes that strengthening the role of community organizations needs to be directed through guidance, training, and regulations that support collaboration with village governments in order to create participatory and responsive village governance.